Handbook of pediatric hematology and oncology : Children's Hospital & Research Center Oakland - Hastings, Caroline , 1960-; Agrawal, Anurag Kishor; Torkildson, Joseph C. (Chichester, West Sussex : Wiley-Blackwell, 2012)
This quick reference guide to the latest diagnostic and therapeutic protocols in pediatric oncology is an invaluable user-friendly resource. The new edition, featuring an attractive two-color text design to highlight key text and algorithms, has been completely updated
Rev. ed. of: The Children's Hospital Oakland hematology/oncology handbook / Caroline Hastings. 1st ed. c2002
Includes bibliographical references and index
Keywords: Pediatric hematology -- Handbooks, manuals, etc; Tumors in children -- Handbooks, manuals, etc; Child; Hematologic Diseases; Neoplasms; Handbooks